1990
DOI: 10.1111/j.1365-2125.1990.tb03596.x
|View full text |Cite
|
Sign up to set email alerts
|

Tianeptine binding to human plasma proteins and plasma from patients with hepatic cirrhosis or renal failure.

Abstract: 1. The binding of tianeptine to human plasma, isolated plasma proteins, red blood cells and to plasma from patients with cirrhosis or renal failure was studied in vitro by equilibrium dialysis. 2. Tianeptine is highly bound to plasma (95%) at therapeutic concentrations (0.3‐1 microM). No saturation of the binding sites was seen. 3. Human serum albumin (HSA) was shown to be mainly responsible for this binding (94%) with a saturable process characterized by one binding site with a moderate affinity (Ka = 4.2 x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Albumin is the most important binding protein for many acidic and basic drugs (26,27 ). The results of our in vitro study suggest that p-cresol also has an affinity for albumin because the in vitro decrease in the BSA concentration led to a higher free fraction of p-cresol (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Albumin is the most important binding protein for many acidic and basic drugs (26,27 ). The results of our in vitro study suggest that p-cresol also has an affinity for albumin because the in vitro decrease in the BSA concentration led to a higher free fraction of p-cresol (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…The ligand loadings of HSA are different for renal and liver insufficiencies [31,32]. However an increase in blood concentration of longchain fatty acids is a common feature for these patients [2,33].…”
Section: Recently Denisov and Hallementioning
confidence: 99%
“…Modified forros o f human serum albumin (HSA) with lowered binding affinity were found in patients with renal and liver failures [1,2]. This results in blocking the H S A binding sites by high concentration o f endogenous hydrophobic and amphiphilic rnetabolites [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral tests in rats [6,7] and clinical trials in man [8,9] have clearly demonstrated the antidepressant activity of this drug. Zini et al [10] were studied the plasma binding of TIA in humans. Ortiz et al [11] were reported the antidepressant drug TIA on plasma and platelet serotonin concentrations in the rat.…”
Section: Introductionmentioning
confidence: 99%